The apoB100/apoAI ratio is independently associated with the severity of coronary heart disease: a cross sectional study in patients undergoing coronary angiography. Issue 1 (December 2015) - Song, Yongyan; Yang, Yang; Zhang, Jingxiao; Wang, Yanmei; He, Wenfeng; Zhang, Xiaoming; Zhu, Jie; Lu, Zhan
Abstract Background Lipoprotein ratios have been shown to be associated with the occurrence of coronary heart disease (CHD), but little is known about their relationships with the severity of CHD. Methods A total of 792 angiographically defined CHD patients were enrolled following their admission. Patients were stratified into three groups based on the tertile of the Gensini scores (≤33rd percentile, 33rd to 66th percentile and ≥66th percentile) or the number of stenotic coronary branches (single-branch stenosis, double-branch stenosis and multi-branch stenosis). Demographic and biochemical data were collected and lipoprotein ratios were calculated. Logistic regression and path analysis were employed to examine the relationships between the lipoprotein ratios and the severity of CHD. Results The ratios of low-density lipoprotein cholesterol (LDL-C)/high-density lipoprotein cholesterol (HDL-C) and apolipoprotein B100 (apoB100)/apolipoprotein AI (apoAI) increased with the tertile of the Gensini scores (P  < 0.05 for both). The ratios of triglyceride (TG)/HDL-C, total cholesterol (TC)/HDL-C, LDL-C/HDL-C and apoB100/apoAI increased with the number of stenotic coronary branches (P  < 0.05 for all). The univariate logistic regression showed that the ratios of TC/HDL-C, LDL-C/HDL-C and apoB100/apoAI were positively associated with both the tertile of the Gensini scores and the number of stenotic vessels (P  < 0.05 for all), and the ratio of TG/HDL-C was positively associated with the number of stenotic vessels (P  < 0.05). In multivariate logistic analysis, only the ratio of apoB100/apoAI was independently and positively associated with the tertile of the Gensini scores (OR = 2.93, 95 % CI = 1.17-7.34, P  = 0.022) and the number of stenotic vessels (OR = 3.14, 95 % CI = 1.01-6.47, P  = 0.048) after adjusting for the possible confounding variables. The apoB100/apoAI ratio was also shown to be a direct mediator between the risk factors including age, BMI, HDL-C, LDL-C, apoB100 and apoAI and the severity of CHD by path analysis. Conclusion Our data indicate that the apoB100/apoAI ratio could be a useful predictor for evaluating the severity of coronary stenosis in CHD patients.